2017
DOI: 10.1051/0004-6361/201629520
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysical properties of star clusters in the Magellanic Clouds homogeneously estimated by ASteCA

Abstract: Aims. We seek to produce a homogeneous catalog of astrophysical parameters of 239 resolved star clusters, located in the Small and Large Magellanic Clouds, observed in the Washington photometric system. Methods. The cluster sample was processed with the recently introduced Automated Stellar Cluster Analysis (ASteCA) package, which ensures both an automatized and a fully reproducible treatment, together with a statistically based analysis of their fundamental parameters and associated uncertainties. The fundame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 112 publications
(96 reference statements)
5
51
1
7
Order By: Relevance
“…As discussed by Kamath et al (2010), the age of the SMC cluster NGC 419 is believed to be around 1.4-1.6 Gyr. This is consistent with the value τ = 1.45 ± 0.05 Gyr from Goudfrooij et al (2014), while it is as young as τ 0.89 ± 0.015 Gyr according to Perren et al (2017). Since an accurate estimate is not necessary for our exploratory analysis, we took a rough average and assumed log(τ/yr) = 9.1 ± 0.1.…”
Section: Datasupporting
confidence: 80%
See 1 more Smart Citation
“…As discussed by Kamath et al (2010), the age of the SMC cluster NGC 419 is believed to be around 1.4-1.6 Gyr. This is consistent with the value τ = 1.45 ± 0.05 Gyr from Goudfrooij et al (2014), while it is as young as τ 0.89 ± 0.015 Gyr according to Perren et al (2017). Since an accurate estimate is not necessary for our exploratory analysis, we took a rough average and assumed log(τ/yr) = 9.1 ± 0.1.…”
Section: Datasupporting
confidence: 80%
“…Distances of Galactic clusters were also taken from Kharchenko et al (2016), while for the Magellanic Clouds and their clusters we adopted the distance moduli µ LMC = 18.49 ± 0.09 mag and µ SMC = 18.96 ± 0.02 mag from de Grijs et al (2017). We searched for data on interstellar extinction from several literature works (e.g., Nayak et al 2016;Kharchenko et al 2016;Perren et al 2017), all of which suggest that extinction in the K s filter is smaller than ∼0.1 mag for most of the clusters we considered, and at most as large as ∼0.3 mag, which is negligible for our purposes.…”
Section: Datamentioning
confidence: 99%
“…More locally, the effects of gas retention on observations of SMC and LMC star clusters has focused predominately on the YMC population (Bastian & Strader 2014;Longmore 2015). While there are IACs in the LMC and SMC with large extinctions there is not an overall trend with age (Perren et al 2017) as would be suggested by the work presented here. However, we caution here that once again LMC and SMC clusters are not necessarily the isolated systems discussed in this work.…”
Section: Prospects For the Detection Of Gas And Star Formation Inmentioning
confidence: 60%
“…We shall limit ourselves to give a brief summary about the way the positional and photometric data are employed by the code. A complete description of Perren et al (2015) and Perren et al (2017). The basic hypothesis of any stellar cluster analysis is that the region occupied by a real cluster and the surrounding field should show "a priori" different properties.…”
Section: Photometric Data Analysis Process: Gaia Data and The Asteca mentioning
confidence: 99%